CCNP ISCW official exam certification guide - Morgan, Brian (Brian Edward) (Cisco Press, 2007)
CCNP ISCW Official Exam Certification Guide Master all 642-825 exam topics with the official study guide Assess your knowledge with chapter-opening quizzes Review key concepts with foundation summaries Practice with hundreds of exam questions on the CD-ROM Brian Morgan, CCIE® No. 4865 Neil Lovering, CCIE No. 1772 CCNP ISCW Official Exam Certification Guide is a best of breed Cisco® exam study guide that focuses specifically on the objectives for the Implementing Secure Converged Wide Area Networks exam (642-825 ISCW). Successfully passing the ISCW 642-825 exam certifies that you have the knowledge and skills necessary to secure and expand the reach of an enterprise network to teleworkers and remote sites with focus on securing remote access and VPN client configuration. CCNP ISCW Official Exam Certification Guide follows a logical organization of the CCNP® ISCW exam objectives. Material is presented in a concise manner, focusing on increasing your retention and recall of exam topics. You can organize your exam preparation through the use of the consistent features in these chapters. "Do I Know This Already?" quizzes open each chapter and allow you to decide how much time you need to spend on each section. Exam topic lists and concise Foundation Summary information make referencing easy and give you a quick refresher whenever you need it. Challenging chapter-ending review questions help you assess your knowledge and reinforce key concepts. The companion CD-ROM contains a powerful testing engine that allows you to focus on individual topic areas or take complete, timed exams. The assessment engine also tracks your performance and provides feedback on a topic-by-topic basis, presenting question-by-question remediation to the text. Well regarded for its level of detail, assessment features, and challenging review questions and exercises, this book helps you master the concepts and techniques that can enable you to succeed on the exam the first time. Brian Morgan, CCIE® No. 4865, is a consulting systems engineer for Cisco, specializing in Unified Communications technologies. He services a number of Fortune 500 companies in architectural, design, and support roles. With more than 15 years in the networking industry, he served as director of engineering for a large telecommunications company, is a certified Cisco instructor teaching at all levels, from basic routing and switching to CCIE lab preparation, and spent a number of years with IBM Network S ...